EXCERPTS FROM THE BNCC: DISCUSSION OF FOUNDATIONS AND CONCEPTUAL CONSIDERATIONS - Lemes, Sebastiao de Souza [UNESP] (Unesp-faculdade Ciencias & Letras, 2021)
In this first excerpt, made in a broad study with some theoretical depth, it aims to discuss some concepts brought by BNCC from excerpts from its foundations. The text seeks, in this way and in the light of a reflective theoretical exploration, to analyze the complexity of this universe for the pedagogical practice in everyday schooling, as it considers certain incompleteness due to the distance between its idealized formulation and the structural and conjunctural reality then presented so that they have their rights to learning and development assured, in accordance with the provisions of the National Education Plan. This theoretical and exploratory study of the concepts and narrative elements present in a document of a normative character and with the degree of instrumental and operational complexity that presents itself, it needs permanent inquiries and reflections about its effectiveness, from the educational system to the school unit.
Keywords: Educational system; Common National Curricular Base; Schooling